Collage and Paper Art Activities and Preschool Children's Reading and Writing Readiness - Zeynep Çetin; Miray Özözen Danacı (Hacettepe University, 2015)
Objective: Collage is a primary artistic activity in preschool. Collage and paper art are very important to children in this period because art helps them to develop their reasoning, creative, imaginative, and problem solving skills. Doing art enhances their motor skills, hand and eye coordination, and helps them to make cognitive advances such as learning proportions. Moreover, as a form of art it enables children to express their feelings, thoughts and wishes freely with voices, drawings and movements. Material and Method: This study collected data by reviewing the literature on preschoolers and collage and paper art and considering current approaches to collage and paper art in preschool educational institutions in our country, in particular, as an important first step in learning how to read and write. Results: After collecting the data, recommendations were made for educators for using collage and paper art activities as a springboard to reading and writing readiness.